Estimated Atmospheric Emissions from Mobile Sources and Assessment of Air Quality in The Urban Area - Teixeira, Elba; Mattiuzi, Camila D. P.; Wiegand, Flavio; Feltes, Sabrina; Norte, Felipe (IntechOpen, 2011)
None